Neutrophil gelatinase-associated lipocalin and symmetric dimethylarginine concentrations in dogs with carcinoma and sarcoma - Pazzi, Paolo (University of Pretoria, 2025)
Mini Dissertation MMedVet (Med)--University of Pretoria, 2024.